The effect of curcumax on postpartum women’s depression: a randomized controlled trial - Nikpour, Fatemeh; Ansari, Somayeh; Abedi, Parvin; Jahanfar, Shayesteh; Sharifat, Naeim; Hooshmand, Gholamreza; Maraghi, Elham (Frontiers in Psychiatry, 2024)
Background: Postpartum depression is a major psychiatric disorder that affects the motherbaby attachment and may impair cognitive development of the child.Objective: This study aimed to evaluate the effect of curcumax (including ginger, turmeric, and black pepper) on postpartum depression in reproductive-aged women.This was a randomized controlled trial in which 124 women were recruited and randomly assigned into two groups of curcumax (n=62) and placebo (n=62) who consumed curcumax or placebo for 8 weeks (one capsule each day). Postpartum depression was measured using Edinburgh Depression Scale. Data were analyzed using Chi-square, independent t-test, ANOVA, and GEE.The mean (SD) score of depression score was 15.83 (2.77) and 15.45 (2.97) before intervention, which reduced to 3.48 (4.29) and 7.22 (3.98) in the intervention and control groups, respectively after 4 weeks (p<0.0001). After eight weeks of intervention, these scores reduced to 1.72 (3.30) and 5.85 (3.67) in the intervention and control groups, respectively (p<0.0001).The results of this study showed that curcumax significantly reduced the mean score of postpartum depression among reproductive-aged women. Because it is the first time this herb was used as an anti-depressant, its effective dose was not available. Therefore, further studies with higher doses of this herb are recommended.